Holocene emergence and shoreline delevelling, southern Eureka Sound, High Arctic Canada - Ó Cofaigh, Colm (Géographie physique et Quaternaire, 1999)
AbstractThis paper is a reconstruction of postglacial relative sea level change and shoreline delevelling in southern Eureka Sound, High Arctic Canada. Postglacial emergence of up to 150 m is recorded in this area by raised marine deltas, beaches and washing limits that date from the early Holocene. Marine limit is metachronous and formed successively with glacier retreat. Marked contrasts in the form of relative sea level curves and rate of initial emergence are recorded from the study area. In Blind Fiord, relative sea level fell continuously following deglaciation. Initial emergence was characterised by rates of ≥ 5 m/century. This contrasts with curves from Starfish and Irene bays, where the rate of initial emergence was ≤ 1 m/century. Isobases drawn on the 8.5 ka shoreline for greater Eureka Sound demonstrate that a cell of highest emergence (≥ 130 m asl) extends along the length of the channel, and closes in the vicinity of the entrance to Norwegian Bay. This pattern confirms a distinct loading centre over Eureka Sound during the Last Glacial Maximum, and is compatible with independent glacial geological evidence indicating that the thickest ice was centred over the channel during the Late Wisconsinan.